The Impact of Indonesia Green Economy in Masterplan for Future Urban Farming Indonesia - Naipospos, Agnes; Azzura, Raia (Lembaga Contrarius Indonesia, 2023)
Indonesia is an agrarian country with 38.70 million people working in the agriculture, forestry, and fisheries sectors, accounting for 28.61% of the total workforce. With a contribution of 12.98 percent to the GDP, agriculture is one of the crucial economic sectors in Indonesia. However, rapid urban development has reduced the vegetable supply, and urban farming in cities can be a solution by utilizing community yards to meet food needs, reduce household expenses, and increase farmer income. Utilizing community yards to meet food needs, reduce household expenses, and increase farmer income, urban farming in cities can be a solution. The research method employs a normative juridical approach, examining elements in positive law and making comparisons with other countries. Based on this approach, the study indicates that amid food issues and a declining interest in farming, Indonesia needs an urban farming program, but the current implementation of the program is not optimal. Therefore, the Indonesia Masterplan for Future Urban Farming (IM-for-FUF) is introduced as an innovation expected to better support the implementation of the green economy within the framework of positive law for sustainable economics in Indonesia. One effort to enhance food availability and environmental quality is the IM-for-FUF. Additionally, the farming concept is unique as it utilizes existing areas, eliminating the need for extensive space. By supporting IM-for-FUF, communities can acquire new skills and knowledge about farming, positively impacting the environment by utilizing the surrounding areas.